2010
DOI: 10.1021/nl102725k
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Metal Nanofiber Webs as High-Performance Transparent Electrode

Abstract: Transparent electrodes, indespensible in displays and solar cells, are currently dominated by indium tin oxide (ITO) films although the high price of indium, brittleness of films, and high vacuum deposition are limiting their applications. Recently, solution-processed networks of nanostructures such as carbon nanotubes (CNTs), graphene, and silver nanowires have attracted great attention as replacements. A low junction resistance between nanostructures is important for decreasing the sheet resistance. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
573
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 678 publications
(591 citation statements)
references
References 33 publications
15
573
1
2
Order By: Relevance
“…In the past decade, it has been also used to produce wires of a variety of inorganic materials 39 . Our group has previously used electrospinning for making Cu nanowires for transparent electrodes 15,16 . Here we extend this method for making larger diameter mesoscale wires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, it has been also used to produce wires of a variety of inorganic materials 39 . Our group has previously used electrospinning for making Cu nanowires for transparent electrodes 15,16 . Here we extend this method for making larger diameter mesoscale wires.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been increasing efforts in developing nanomaterial TCEs including carbon nanotubes (CNTs) 1,[6][7][8][9] , graphene 4,[10][11][12][13] , metal nanowires [14][15][16][17][18][19][20][21] and nanoparticles 22,23 to replace conventional indium tin oxide (ITO) films, in order to enable low-cost and mechanical flexibility while maintaining low sheet resistance (R s ) and high transmittance (T). For the active layers of many devices, the lateral surface electrical conductance is sufficient to transport electrons only locally from several 100 nm to a few mm scale without serious ohmic loss, therefore interfacing with external connection requires additional TCEs with good R s -T performance.…”
mentioning
confidence: 99%
“…One very promising technique is the employment of a mesh structure with periodic lines on the rGO film [53], with OSC devices based on graphene mesh electrodes (GMEs) already exhibiting performances comparable to those using conventional ITO TCEs [54,55]. Therefore, it is possible to control the films R s and transparency by tailoring the grid width, spacing, and thickness [56].…”
Section: Photochemically Treated Rgo Transparent Conductive Electrodesmentioning
confidence: 99%
“…Instead of the metal grid, which has a complicated fabrication process and relatively poor stretchability, several methods of creating stretchable transparent electrodes based on metal nanofibers have been developed [58][59][60][61][62][63][64]. Among them, electrospinning is a method that is optimized to make continuous one-dimensional nanomaterials with polymers, oxides, and carbon [65,66].…”
Section: Metal Nanofibersmentioning
confidence: 99%
“…Cui et al demonstrated a random network of Cu nanofibers by electrospinning copper acetate melt in poly(vinyl acetate), as shown in Figure 3(a). After the electrospinning, the fibers were successively annealed at 300°C and 500°C [58]. This increased the aspect ratio of the nanofiber to ∼ 10 6 , and 50 /sq sheet resistance at 90% transmittance was obtained due to the fused junctions within the metal nanofiber networks.…”
Section: Metal Nanofibersmentioning
confidence: 99%